2019
DOI: 10.1152/japplphysiol.01116.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation enhances cerebrovascular CO2 reactivity in a sex-specific manner

Abstract: Insufficient nitric oxide (NO) bioavailability plays an important role in endothelial dysfunction, and increased NO has the potential to enhance cerebral blood flow (CBF). Dietary supplementation with sodium nitrate, a precursor of NO, could improve cerebrovascular function, but this has not been investigated. In 17 individuals, we examined the effects of a 7-day supplementation of dietary nitrate (0.1 mmol·kg−1·day −1) on cerebrovascular function using a randomized, single-blinded placebo-controlled crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 73 publications
1
21
1
Order By: Relevance
“…4D-MRI analysis of the major cerebral arteries during hypercapnia has found young males to have a greater cerebral vascular reactivity than young females (Miller et al, 2019). However, this finding is not consistent especially in studies that have measured CBF with TCD (Fan et al, 2019;Madureira et al, 2017;Peltonen et al, 2015). In our study, the ΔEtCO 2 responses were similar between the sexes as exercise intensity increased (Figure 2h).…”
Section: Cvci Response To Gxtcontrasting
confidence: 79%
See 2 more Smart Citations
“…4D-MRI analysis of the major cerebral arteries during hypercapnia has found young males to have a greater cerebral vascular reactivity than young females (Miller et al, 2019). However, this finding is not consistent especially in studies that have measured CBF with TCD (Fan et al, 2019;Madureira et al, 2017;Peltonen et al, 2015). In our study, the ΔEtCO 2 responses were similar between the sexes as exercise intensity increased (Figure 2h).…”
Section: Cvci Response To Gxtcontrasting
confidence: 79%
“…Doing this allowed for comparison of models and to aid in the explanation of cerebrovascular differences between males and females. Comparing the sex-specific model β coefficients using a Z score (Paternoster et al, 2016) (Fan et al, 2019;Kastrup et al, 1998); however, this is not universally accepted (Miller et al, 2019;Peltonen et al, 2015). This analysis is in line with the former, showing females increased MCAv to a greater extent for every change in EtCO 2 (mmHg), Table 3 and Table 4.…”
Section: Explaining Cerebral Blood Flow Responsesupporting
confidence: 51%
See 1 more Smart Citation
“…Previous research has shown the thigh-cuff method, which imposes a large and abrupt change in blood pressure, is more sensitive to interventions, such as hypoxia, than transfer function analysis that examines spontaneous fluctuations in blood pressure. 26 The importance of using these methods is emphasised when considering the only other study to have examined dietary nitrate supplementation on dynamic CA in normoxia reported inconclusive effects 31 that may have resulted from using TCD and transfer function analysis, which is a less sensitive method to assess dynamic CA than used in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…Dietary and pharmacologic strategies that improve NO bioavailability have been shown to improve CVR. Seven days of dietary nitrate supplementation (an NO donor) improves CVR in young adults in a sex-specific manner (Fan et al, 2019). In a similar vein, statins have also improved CVR (Sander et al, 2005), likely through a NO-dependent mechanism (Yamada et al, 2000).…”
Section: Endothelial Dysfunctionmentioning
confidence: 97%